Merdeka Curriculum Implementation at Secondary Schools: Science Teachers’ Perspective - Melani Tasya Putri; Ogi Danika Pranata (Universitas Muhammadiyah Mataram, 2024)
This study examines the challenges in implementing the Merdeka Curriculum in science education at a high school in Sungai Penuh City and a Madrasah Aliyah in Kerinci Regency. Using a qualitative approach through interviews and observations, this study reveals that although most science teachers support the curriculum changes and recognize its potential benefits, there are significant obstacles in their readiness and adaptation to new methods. Key challenges such as limited technological proficiency, reliance on traditional teaching methods, and inadequate facilities impact the effectiveness of curriculum implementation. The study’s findings also show variation in the use of technology, with some teachers utilizing tools like projectors and various educational applications, while others continue to rely on conventional approaches. To enhance the implementation process, this study recommends more focused and directed professional development, increased access to technological resources, and better alignment between teaching methods and curriculum goals. Strengthening these areas is essential to overcoming current challenges and improving the quality of science education under the Merdeka Curriculum. Thus, the results of this study can contribute to guiding strategic steps to enhance teaching practices nationwide, aiming to achieve a more inclusive and adaptive education aligned with the vision of the Merdeka Curriculum.